Microbiota from Obese Mice Regulate Hematopoietic Stem Cell Differentiation by Altering the Bone Niche - Luo, Yubin; Chen, Guangliang; Hannemann, Nicole; Ipseiz, Natacha; Krönke, Gerhard; Bäuerle, Tobias; Munos, Luis; Wirtz, Stefan; Schett, Georg; Bozec, Aline (Cell Metabolism, 2015)
The effect of metabolic stress on the bone marrow microenvironment is poorly defined. We show that high-fat diet (HFD) decreased long-term Lin(-)Sca-1(+)c-Kit(+) (LSK) stem cells and shifted lymphoid to myeloid cell differentiation. Bone marrow niche function was impaired after HFD as shown by poor reconstitution of hematopoietic stem cells. HFD led to robust activation of PPAR?2, which impaired osteoblastogenesis while enhancing bone marrow adipogenesis. At the same time, expression of genes such as Jag-1, SDF-1, and IL-7 forming the bone marrow niche was highly suppressed after HFD. Moreover, structural changes of microbiota were associated to HFD-induced bone marrow changes. Antibiotic treatment partially rescued HFD-mediated effects on the bone marrow niche, while transplantation of stools from HFD mice could transfer the effect to normal mice. These findings show that metabolic stress affects the bone marrow niche by alterations of gut microbiota and osteoblast-adipocyte homeostasis.
EVALuna2:1968